THEORETICAL ASPECTS OF TEACHING SUBJECTS IN AN E-LEARNING ENVIRONMENT - Asadova Yulduz Ismatovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article is compiled in theoretical aspects of teaching subjects in an e-learning environment accordance with the information technology science program in education, the methodology for using electronic platforms for students to master independent educational hours allocated to subjects in the conditions of a modular credit system in higher education institutions, in addition, students also have the opportunity to use electronic platforms in educational training sessions in the process of mastering independent educational topics From this article, the student receives the advice he needs and the answer to the questions he search article can be used in the organization of Independent Education of students in all institutions of higher education.